China in and beyond the headlines - Weston, Timothy B., 1964-; Jensen, Lionel M. (China beyond the headlines ;, 2012)
In the third volume of this popular series, leading experts provide fascinating and unexpected insights into critical issues in today's China. They address such key topics as civil society, consumerism, environmental adversity, ethnic tension, the Internet, legal reform, new media and social networking, nationalist tourism, sex, and popular culture, as well the costs of urban gigantism, to portray the complexity of life in contemporary China-and how, increasingly, it speaks to the everyday experience of Americans.